2012
DOI: 10.2134/agronj2012.0035
|View full text |Cite
|
Sign up to set email alerts
|

Sowing Method Effects on Clover Establishment into Permanent Pasture

Abstract: E stablishing clover (Trifolium spp.) into permanent pasture can be challenging, because many factors like competition from existing the sward, subsequent grazing management, or weather fl uctuations can aff ect this process. Two common overseeding methods for clover include surface sowing without disturbance (broadcasting) or drilling of seed through undisturbed sod and residue (Pearson and Ison, 1997). Frost-seeding is a form of overseeding when seed is broadcasted mid-winter on top of snow and frozen ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 27 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…The data suggest that red clover plants that were established in the short stubble vegetation in 2010 were still the primary contributors to yield the following year. This result confirms the idea that over seeding clover into short residual stubble is a critical element for successful establishment and to ensure subsequent contribution to yield (Schlueter and Tracy ). The response of red clover to the higher defoliation frequency was surprising though as several studies have shown that growth can be negatively affected by frequent defoliation (Sheldrick et al .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The data suggest that red clover plants that were established in the short stubble vegetation in 2010 were still the primary contributors to yield the following year. This result confirms the idea that over seeding clover into short residual stubble is a critical element for successful establishment and to ensure subsequent contribution to yield (Schlueter and Tracy ). The response of red clover to the higher defoliation frequency was surprising though as several studies have shown that growth can be negatively affected by frequent defoliation (Sheldrick et al .…”
Section: Resultssupporting
confidence: 86%
“…Successful clover establishment in grass swards clearly depended on reducing grass competition at sowing and frequent defoliation. While not a surprising result, our data indicate that clover establishment is contingent on both processes (Schlueter and Tracy 2012). In other words, frequent defoliation alone probably will not improve clover establishment unless the initial grass competition is greatly reduced at sowing and vice versa.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…like the WSG pastures previous to conversion and had been used for grazing experiments as described by Schlueter and Tracy (2012). A hydraulic soil corer (Giddings Machine Company) was used to collect soil samples 6.35 cm in diameter by 40 cm.…”
Section: Soil Carbon Measurementsmentioning
confidence: 99%
“…The CSG pastures were dominated by tall fescue and clovers (Trifolium spp.) like the WSG pastures previous to conversion and had been used for grazing experiments as described by Schlueter and Tracy (2012). Soils were dried at 105°C until a constant weight was reached.…”
Section: Soil Carbon Measurementsmentioning
confidence: 99%